Influence of maximum power output on speech understanding with bone anchored hearing systems. (3rd March 2020) - Gawliczek, Tom; Wimmer, Wilhelm; Caversaccio, Marco; Kompis, Martin
Abstract: Background: Maximum power output (MPO) levels of bone anchored hearing systems (BAHS) vary between different devices, but are significantly lower than those of conventional hearing aids, potentially limiting speech understanding. Aims/objectives: To investigate, how MPO influences speech understanding in quiet and in noise in BAHS users. Materials and methods: 12 adult BAHS users with a bilateral conductive hearing loss and additional sensorineural hearing components between 4 and 45 dB (500–4000 Hz) participated in the study. Speech understanding was measured at 65 dB in quiet and in noise with 4 different MPO level settings, covering the approximate range of MPOs found in currently available BAHS devices. Results: Speech understanding in quiet and in noise decreased with increasing sensorineural hearing loss. MPOs levels did not influence speech understanding in quiet significantly. In contrast, speech understanding in noise was better with higher MPOs (average improvement in signal-to-noise ratio +3.2 dB, p  < .001), but only if the sensorineural hearing loss component was above approximately 35 dB. Conclusions and significance: At normal conversational levels, higher MPOs have little or no influence on speech understanding in quiet with BAHS. However, they can improve speech understanding in noise for users with additional sensorineural hearing loss.